Preaching Prophets: Upton Sinclair and The Moslem Sunrise - Steven Bembridge (European Journal of American Studies)
In 1920, Mufti Muhammad Sadiq (1872–1957) arrived in America to spread the message of Islam. Two years later, he founded The Moslem Sunrise. The October 1922 issue included a review of Upton Sinclair’s (1878–1968) serialized story “They Call Me Carpenter.” In Sinclair’s work, Jesus, or Carpenter, returns to live amongst modern Americans. This article explores the theological and cultural contexts that led The Moslem Sunrise to find an affinity in Sinclair’s work. It explores how and why The Moslem Sunrise and Sinclair each addressed the Christology of a human Jesus, the perceived failure of the Church to teach his social gospel, the concept of human brotherhood, and the perceived need to masculinise religion—and even Jesus himself and his associated ethnicity. It reveals a previously unacknowledged relationship between Islam and Sinclair and demonstrates how quite different processes can sometimes lead to unity and to a shared direction.